Strategi pemahaman literasi keuangan syariah kepada pelaku usaha UMKM - Marom, Ahmad Aufal (Maliki Interdisciplinary Journal, 2025)
Increasing sharia financial literacy in Micro, Small and Medium Enterprises (MSMEs) in Indonesia is very important, considering that MSMEs play a significant role in the national economy with a contribution of more than 60% to GDP. However, MSMEs still face obstacles in accessing finance and low understanding of finance. Sharia finance can be a solution that is in line with Islamic principles, but the level of understanding about it is still limited. Increasing sharia financial literacy will help MSMEs more easily access financing, manage finances better, and encourage innovation in sharia financial products. For this reason, collaboration is needed from various parties to increase sharia financial literacy so that MSMEs can make optimal use of sharia financial services in developing their businesses.